2015
DOI: 10.1155/2015/819146
|View full text |Cite
|
Sign up to set email alerts
|

Previous Preterm Birth and Current Maternal Complications as a Risk Factor of Subsequent Stillbirth

Abstract: properly cited.Purpose. To examine the association between previous preterm birth and the risk of stillbirth. Methods. This population-based retrospective cohort study analyzed live births and stillbirth records in Missouri (1989Missouri ( -1997. The main outcome of interest was stillbirth occurrence while the exposures were prior preterm birth. Adjusted odds ratios and 95% confidence intervals were computed using logistic regression. Results. Women who had a previous preterm birth have 63% increased odds of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A finding supported by a study in Australia, which showed that having diabetics mellitus and hypertension prior to pregnancy were associated with increased risk for stillbirth with mixed results for preeclampsia and eclampsia which were both found to raise the risk for antepartum stillbirth (Ibiebele et al, 2017). Ibrahimou et al, (2015), in a study in USA, showed that antepartum stillbirth was associated with various conditions that included eclampsia, hypertension, diabetes, multiple gestations and placenta abruptions that often result into premature termination of pregnancy.…”
Section: Literature Reviewmentioning
confidence: 85%
“…A finding supported by a study in Australia, which showed that having diabetics mellitus and hypertension prior to pregnancy were associated with increased risk for stillbirth with mixed results for preeclampsia and eclampsia which were both found to raise the risk for antepartum stillbirth (Ibiebele et al, 2017). Ibrahimou et al, (2015), in a study in USA, showed that antepartum stillbirth was associated with various conditions that included eclampsia, hypertension, diabetes, multiple gestations and placenta abruptions that often result into premature termination of pregnancy.…”
Section: Literature Reviewmentioning
confidence: 85%
“…In general, multiple factors could result in stillbirth, which can generally be categorized as maternal, fetal, and facility-level factors (25). Congenital malformation, infection, gestational age, sex, and birth weight are the fetal factors related to stillbirth (26)(27)(28)(29)(30), while maternal health conditions before and during pregnancy, maternal age, maternal parity, history of ANC visit, mode of delivery, maternal education, wealth index, birth interval, previous history of stillbirth, fetal movement monitoring are the major maternal factors (31)(32)(33)(34)(35). On the other hand, factors such as intrapartum monitoring, clinical management, and capacity of diagnosis are some of the facility-level predictors of stillbirth (36).…”
Section: Introductionmentioning
confidence: 99%